[Human papillomavirus cervical infection: viral genotyping and risk factors for high-grade squamous intraepithelial lesion and cervix cancer]. - de Mendonça, Vilma Guimarães; Guimarães, Maria José Bezerra; de Lima Filho, José Luiz; de Mendonça, Carolina Guimarães; Martins, Danyelly Bruneska Gondim; Crovella, Sergio; de Alencar, Luiz Cláudio Arraes (Rev Bras Ginecol Obstet, 2010)
PURPOSE: to analyze the characteristics of viral infection and the risk factors for high-grade squamous intraepithelial lesion and cervical carcinoma in women with cervical HPV infection. METHODS: a case-control study was conducted on women with cervical HPV at a Gynecology reference service enrolled at the Public Health System, located in Recife, Northeastern Brazil. The groups of cases (72 women with high-grade squamous intraepithelial lesion or cervical cancer) and controls (176 women with normal Pap smear or benign alterations) were investigated for six viral genotypes (HPV 16, 18, 31, 33, 6, 11) in ecto- and endocervical material using MY09/MY11 primers. The independent variables were ranked in three levels of determination: distal (sociodemographic), intermediate (behavioral) and proximal (previous Pap smear). The homogeneity of proportions was tested (χ2), unadjusted Odds Ratios (OR) were obtained and hierarchical logistic regression was applied to the final model, with adjustment of the effect of each variable to the outcome based on the variables in the same and previous levels of causality. RESULTS: the viral genotype of cervical infection was identified in 76.6% of the 248 women participating in the study. High-risk HPV genotypes (83.4% of cases and 67.1% of controls) were predominant, especially HPV 16 and 31. The distal risk factors identified were: living in a rural area (OR=2.71, 95%CI: 1.18-6.23), less than three years of study (OR=3.97, 95%CI: 2.09-7.54) and family income below two minimum wages (OR=3.30, 95%CI: 1.04-10.51); intermediate: four or more pregnancies (OR=2.00, 95%CI: 1.06-3.76); and proximal: absence of a previous Pap smear (OR=9.74, 95%CI: 2.48-38.28). CONCLUSIONS: genotypes 16 and 31 of cervical HPV infection are predominant among women assisted by the Public Health System in Northeastern Brazil. Socioeconomic and reproductive factors, as well as the absence of cytological screening, represent risk factors for the progression of infection to high-grade squamous intraepithelial lesion and cervical cancer.
Keywords: Adult; Carcinoma in Situ; Case-Control Studies; Female; Genotype; Humans; Papillomaviridae; Papillomavirus Infections; Risk Factors; Socioeconomic Factors; Uterine Cervical Neoplasms